2019
DOI: 10.1111/btp.12714
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conspecific density, herbivory, and bamboo on seedling dynamics of a dominant oak in a Neotropical highland forest

Abstract: Conspecific negative density dependence (CNDD) is one of the main mechanisms influencing diversity maintenance in tropical forests. Tropical highland forests, in contrast to most lowland forests, are commonly dominated by a few tree species, and testing the importance of density dependence effects on seedling establishment of dominant trees may provide insights on the mechanisms regulating population dynamics and forest composition of tropical highlands. We tested the effect of CNDD regulation on seedling surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Furthermore, several studies in tropical forests demonstrate that lianas can invest more in‐depth roots than in above‐ground growth during the sapling stage, increasing their ability to survive against physical damages and competition (Martínez‐Izquierdo et al, 2016; Restom & Nepstad, 2004; Schnitzer, 2005; Swaine & Grace, 2007). The ability to recover from disturbances, such as trampling or leaf consumption, might also explain why bamboos were not affected by the experimental exclusion of LMH (Buckingham et al, 2011; Calderón‐Sanou et al, 2019; Terborgh et al, 2008). Bamboos possibly have low attractiveness for herbivores, and their solid biomechanical structures, as well as vegetative regeneration and propagation, might additionally contribute to regeneration from LMH disturbance (Rother et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies in tropical forests demonstrate that lianas can invest more in‐depth roots than in above‐ground growth during the sapling stage, increasing their ability to survive against physical damages and competition (Martínez‐Izquierdo et al, 2016; Restom & Nepstad, 2004; Schnitzer, 2005; Swaine & Grace, 2007). The ability to recover from disturbances, such as trampling or leaf consumption, might also explain why bamboos were not affected by the experimental exclusion of LMH (Buckingham et al, 2011; Calderón‐Sanou et al, 2019; Terborgh et al, 2008). Bamboos possibly have low attractiveness for herbivores, and their solid biomechanical structures, as well as vegetative regeneration and propagation, might additionally contribute to regeneration from LMH disturbance (Rother et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Q. costaricensis and H. irazuense appear to be poorly protected against ant herbivory, and in Costa Rica, they occur only at elevations higher than the ants, despite the better growth observed among the temporary surviving seedlings at lower elevations in our study (~ 2000 m a.s.l., Supporting information). Previous observations in the region suggested that survival of Q. costaricenses is often determined by herbivory (Calderón‐Sanou et al 2019). Similarly, the good survival of P. caerulea above its natural range may reflect an absence of specialized herbivores, such as the avocado moth ( Stenoma catenifer ; Luna et al 2017), though at these elevations the seedlings grow slowly.…”
Section: Discussionmentioning
confidence: 99%
“…The vegetation in the adjacent Montane Forests is dominated by oaks ( Quercus costaricensis Liebm.) with abundant epiphytes and shrubs and many species in the Ericaceae, Asteraceae, and Onagraceae [ 66 ].…”
Section: Methodsmentioning
confidence: 99%